ANALISIS AKAD PEMBIAYAAN MURABAHAH PERUMAHAN (KPR) PADA PT BANK BRI SYARIAH KC BANDA ACEH - Yuranda, Alghiffari; Daud, Rulfah M (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This studyains aims to determine how the suitability of handling Murabaha financing problem house loan product at fatwa of the National Sharia Supervisory Board Of The Indonesian Ulama Council (DSN-MUI) in Bank BRI Sharia Banda Aceh. The object of the study are Bank Bri Sharia competent Account Officer which competent in murabaha financing. This study used qualitative descriptive approach. The researcher collected the data by interviewing a account officer of Bank BRI Sharia. The results of this research show murabaha financing of house loan product are suitable with fatwa of the National Sharia Supervisory Board Of The Indonesian Ulama Council (DSN-MUI).